Transformational Leadership, Organizational Resilience, and Team Innovation Performance: A Model for Testing Moderation and Mediation Effects - Jiayu Yu; Kaibiao Xiang (Behavioral Sciences)
This study adopts transformational leadership as the research subject and aims to explore the effect of transformational leadership on organizational resilience and team innovation performance: to test the mediating role of organizational resilience between transformational leadership and team innovation performance, as well as to examine the moderating role that environmental uncertainty performs in the process of the mediation. By analyzing the data collected from a questionnaire, this research discovered that transformational leadership has a positive effect on team innovation performance, which is mediated by organizational resilience. This relationship is more significant when environmental uncertainty is considered as a moderator in the mediation process. Ultimately, based on the findings illustrated above, this study provides suggestions to improve team innovation performance by developing transformational leadership capabilities and awareness, enhancing the business environment, boosting organizational resilience, and increasing the resilience of enterprises in the context of environmental uncertainty. The contribution of this research is demonstrated by the provision of a set of scientifically grounded recommendations for the administration of organizations and enterprises in underdeveloped regions of China.